Comparative evaluation of in vitro performance of commercial and fabricated sustained release diclofenac sodium tablets - Mishra B. (My University, 2025)
Ten commercial sustained release (SR) tablets of diclofenac sodium (DS) were evaluated for in vitro release characteristics in pH 7.4 medium.The rate and extent of drug release were highly variable for these tablets. Five batches of sustained and controlled release matrix tablet of DS were fabricated using polymers, like carboxymethyl cellulose (CMC) or carbopol 974P (Carbopol) alone or in combinations using different ratios, and were evaluated for physical characteristics and drug release performance. The results clearly indicated that batches prepared with admixed polymers exhibited more sustained and controlled release of DS in comparison to most of the commercial tablets. The treatment of data for zero-order, first-order and Higuchi's square root of time equations showed that all the fabricated tablets provided zero-order drug release profiles.